Occurrence of faecal endoparasites in reindeer (Rangifer tarandus) in two grazing areas in northern Norway - Idland, Lene; Juul, Amalie Moen; Solevåg, Ellen Karin; Tysnes, Kristoffer; Robertson, Lucy; Utaaker, Kjersti Selstad (Acta Veterinaria Scandinavica, 2021)
publishedVersion